2022
DOI: 10.3390/rs14153661
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Dust Storm Sources, Affected Areas, and Moving Paths in Mongolia and China in Early Spring

Abstract: Dust storms are common in Mongolia and northern China, this is a serious threat to the ecological security and socioeconomic development of both countries and the surrounding areas. However, a complete quantitative study of the source area, affected area, and moving path of dust storm events (DSEs) in Mongolia and China is still lacking. In this study, we monitored and analyzed the spatiotemporal characteristics of the source area and affected areas of DSEs in Mongolia and China using the high-spatiotemporal-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The Hysplit4 trajectory model, a Eulerian-Lagrangian hybrid model, was employed to analyze the trajectory, diffusion, and sedimentation of air particles [26]. The model has been widely used in numerous studies, including those involving spatial diffusion of pollutants [27][28][29][30][31], water vapor transport [32][33][34], and STE [35,36].…”
Section: Trajectory Analysis Methodsmentioning
confidence: 99%
“…The Hysplit4 trajectory model, a Eulerian-Lagrangian hybrid model, was employed to analyze the trajectory, diffusion, and sedimentation of air particles [26]. The model has been widely used in numerous studies, including those involving spatial diffusion of pollutants [27][28][29][30][31], water vapor transport [32][33][34], and STE [35,36].…”
Section: Trajectory Analysis Methodsmentioning
confidence: 99%
“…Moreover, China has been severely affected by SDSs. Studies have shown that the majority of the SDSs affecting China originate from Mongolia [5][6][7]. Bao et al [6] reported that, during 1977−2018, approximately 50% of the total spring dust days in China were attributable to cross-border SDSs originating from Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Using Medium-Resolution Imaging Spectrometer (MODIS) data, Zhang and Wang [21] reported that, on the Mongolian Plateau, the area most frequently affected by SDSs is mainly the Gobi Desert region straddling Mongolia and Northern China. Bao et al [7] analyzed the spatial distribution and affected areas of cross-border SDSs using Himawari-8/9 remote sensing image data. Based on the movement paths of the dust events between neighboring regions, they found that approximately 55% of the dust events in Inner Mongolia originated from Mongolia, while approximately 60% of the dust events in Mongolia developed locally.…”
Section: Introductionmentioning
confidence: 99%
“…Dust weather, conversely, refers to meteorological disasters in which strong winds sweep over deserts or arid surfaces, causing dust to be swept into the air, in turn reducing visibility [5]. Dust weather can be categorized into floating dust, blowing dust, dust storms, and severe dust storms, based on visibility level [6]. Among them, floating dust and blowing dust are weak dust weather, while dust storms and severe dust storms are strong dust weather [7,8].…”
Section: Introductionmentioning
confidence: 99%